2014
DOI: 10.1182/blood-2014-02-557132
|View full text |Cite
|
Sign up to set email alerts
|

Acquired von Willebrand syndrome: von Willebrand factor propeptide to von Willebrand factor antigen ratio predicts remission status

Abstract: Key Points• Remission status in relapsingremitting AVWS depends on the balance of VWF clearance by anti-VWF antibody and VWF secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…By following up the patient over time, a decrease in the VWFpp/VWF:Ag was observed, along with the normalization of VWF measurements that occurred one month after the beginning of the immunosuppressive therapy. The baseline results of the VWFpp/VWF:Ag measurement facilitated the differential diagnosis between VWD and AVWS, and evaluation over time confirmed the efficacy of the immunological treatment and the remission of the underlying disease, previously undiagnosed 12. It has been already reported that the eradication of the autoantibodies with an aggressive immunosuppression therapy is critical for the treatment of underlying autoimmune disorders, 1 as confirmed herewith.…”
supporting
confidence: 76%
“…By following up the patient over time, a decrease in the VWFpp/VWF:Ag was observed, along with the normalization of VWF measurements that occurred one month after the beginning of the immunosuppressive therapy. The baseline results of the VWFpp/VWF:Ag measurement facilitated the differential diagnosis between VWD and AVWS, and evaluation over time confirmed the efficacy of the immunological treatment and the remission of the underlying disease, previously undiagnosed 12. It has been already reported that the eradication of the autoantibodies with an aggressive immunosuppression therapy is critical for the treatment of underlying autoimmune disorders, 1 as confirmed herewith.…”
supporting
confidence: 76%
“…after administration of VWF concentrate. The presence of anti-VWF antibodies is confirmed by VWFpp and VWFpp/ /VWF: Ag ratio [53].…”
Section: Discussionmentioning
confidence: 87%
“…In 2014, Lee et al [53] described changes in VWFpp/VWF: Ag ratio during the course of treatment of a patient with anti-VWF inhibitor antibodies. At first diagnosis, VWF: RCo, VWF: Ag ratio and FVIII were indeterminate, VWFpp/ /VWF: Ag ratio markedly increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VWFpp is cleaved in the trans-Golgi but remains stored together with mature VWF in platelet α-granules and endothelial cell Weibel-Palade bodies in equimolar amounts. After release, VWFpp dissociates from the mature VWF subunit, circulates with a steady-state half-life, and serves as a marker of VWF secretion 10. A high VWF:pp/Ag ratio has been proposed by Scott et al,11 as a simple method to distinguish AVWS due to decreased VWF synthesis from that due to increased clearance.…”
Section: Discussionmentioning
confidence: 99%